Prospective Evaluation of Kidney Function in Long-Term Survivors of Pediatric CNS Tumors - Natalia Stepien; Viktoria Handler; Johannes Gojo; Amedeo A. Azizi; Lisa Mayr; Chryssa Grylli; Daniela Schwarz; Monika Chocholous; Irene Slavc; Michael Boehm; Andreas Peyrl (Current Oncology, 2022)
Purpose: Numerous acute effects of chemotherapeutics on kidney function are well described. However, data on the long-term effects of chemotherapy in the growing population of childhood central nervous system (CNS) tumor survivors is limited. We aimed to evaluate the kidney function of a cohort of long-term CNS tumor survivors treated with different standard chemotherapeutic regimens. Methods: Patients treated for a CNS tumor were prospectively evaluated up to 12 years after completion of their therapy. Examination of kidney function was performed during routine follow-up visits. Blood pressure and blood and urine parameters were analyzed for kidney function evaluation. Glomerular function was assessed by calculating the estimated glomerular filtration rate (eGFR), tubular functions were analyzed by measuring serum electrolytes, bicarbonate and phosphate reabsorption, and proteinuria was assessed by calculating the protein/creatinine ratio and phosphate reabsorption. Results: None of the 65 patients evaluated suffered from clinically relevant kidney impairment (eGFR < 90 mL/min/L, 73 m2). There was no association between chemotherapy dose and eGFR. Only two patients showed mild signs of tubulopathy and 11 patients were diagnosed with elevated blood pressure. Conclusion: With adequate supportive measures, such as sufficient hydration according to chemotherapy protocol guidelines, as well as avoidance or close monitoring of additional nephrotoxic medication, impaired kidney function is rare in CNS tumor survivors treated with standard chemotherapy. Nonetheless, long-term follow-up is essential for early detection of mild impairment of kidney function.